Amelioration of phytotoxic impact of biosynthesized zinc oxide nanoparticles Plant growth promoting rhizobacteria facilitates the growth and biochemical responses of Eggplant (Solanum melongena) under nanoparticles stress - Solanki, Bushra (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.